Nomenclature and characterization of leukocyte differentiation antigens in ruminants - Naessens, Jan; Howard, C.J.; Hopkins, J. (Elsevier, 1997)
Three international workshops held over the past eight years have addressed the identification and nomenclature of leukocyte differentiation antigens in ruminants. This article explains the progress the workshops have made.